Determinación cuantitativa de polifenoles y metabolitos con propiedades antioxidantes en el extracto de altamisa (Ambrosia artemisiifolia) - Criollo Maldonado, Angélica Andrea (2015)
The present investigation was to identify the antioxidant action of Altamisa (Ambrosia artemisiifolia), the study began with the collection, washing, drying and grinding leaves Altamisa, later to carry out the organoleptic and physico-chemical analysis, thereby determining the compliance with established quality parameters to produce an aqueous extract.